Childhood overweight and obesity in the regional hospital of moquegua: obrepeso y obesidad infantil en el hospital regional moquegua - Medina Valdivia, José (2019)
Objective: To establish the prevalence, epidemiology and clinical, biochemical characteristics and images of overweight and obesity in children from 5 to 10 years of age attended in outpatient pediatrics of the Moquegua Regional Hospital between the months of August to December 2017. Methods: A descriptive, observational, cross-sectional study was carried out; a database was created in the SPSS version 23 program, descriptive statistics were used to determine if there were significant differences between the variables Chi square was used. Results: Of a total of 170 children from 5 to 10 years of age attended in the outpatient clinic of pediatrics of the Moquegua Regional Hospital, 88 children (51.8%) were found with overweight and obesity according to the WHO 2007 Diagnostic criteria; 36 children (21.2%) with overweight and 52 children (30.6%) with obesity. Conclusion: The present study shows an increase in the prevalence of overweight and obesity in children from 5 to 10 years old, with epidemiological, clinical, biochemical, ultrasound and radiographic images very important to develop non communicable diseases such as diabetes, hypertension, dyslipidemias, cancer, metabolic syndrome, among others, causing an inadequate quality of life, resulting in a public health problem and therefore an increase in morbidity and mortality in our Moquegua Region. DOI:10.25176/RFMH.v19.n2.2069